The impact of secondhand smoke on the development of kidney stone disease is not inferior to that of smoking: a longitudinal cohort study - Yi-Hsuan Chen; Jia-In Lee; Jung-Tsung Shen; Yi-Hsuan Wu; Yao-Hsuan Tsao; Jhen-Hao Jhan; Hsun-Shuan Wang; Yung-Chin Lee; Shu-Pin Huang; Szu-Chia Chen; Jiun-Hung Geng (BMC, 2023)
Abstract Background Tobacco use and secondhand smoke (SHS) are risk factors of kidney stone disease (KSD). The hypothesis is that tobacco produces chemicals that increase oxidative stress and vasopressin, which leads to decreased urine output, and contributes to stone formation. The aim of this study was to examine the effects of smoking and SHS on the development of KSD. Materials and methods We analyzed a total of 25,256 volunteers with no history of KSD participated in the Taiwan Biobank. The presence of underlying and follow-up KSD was surveyed by a self-administrated questionnaire. They were classified into three groups on the basis of smoking and SHS exposure, accessed with survey questionnaires; never-smokers with no SHS exposure, never-smokers with SHS exposure and ever-smokers groups. Results KSD was noted in 352 (2.0%), 50 (3.3%) and 240 (4.1%) subjects in the never-smokers with no SHS exposure, never-smokers with SHS exposure and ever-smokers groups, respectively, with a mean follow-up of 4 years. The odds ratio (OR) of KSD was higher in the never-smokers with SHS exposure (OR, 1.622; 95% confidence interval [95% CI], 1.225 to 2.255) and ever-smokers groups (OR, 1.282; 95% CI, 1.044 to 1.574) than in the never-smokers with no SHS exposure group after adjustment of confounders. In addition, never-smokers with SHS exposure had similar effects on the development of KSD than ever-smokers (OR, 1.223; 95% CI, 0.852 to 1.756). Conclusion Our study suggests that both smoking and SHS are a risk factor for developing KSD and that the impact of SHS is not inferior to that of smoking. Trial registration The study was conducted in accordance with the Declaration of Helsinki and approved by the Institutional Review Board of Kaohsiung Medical University Hospital (KMUHIRB-E(I)-20,210,058).